Morphology-driven superhydrophobic polystyrene webs: fabrication and characterization - Yuan, Yue (Kansas State University, 2016)
Superhydrophobicity (water contact angle, WCA >150˚) can be achieved by introducing surface roughness and decreasing surface energy. Polystyrene (PS) electrospun web can be used as an excellent substrate for superhydrophobic surface due to its low surface energy (~33 mN/m) and processibility to form various roughness. As the Cassie-Baxter model explains, the presence of roughness amplifies anti-wettability of materials whose surface energy is low (hydrophobic, WCA >90˚). This study aims to fabricate superhydrophobic PS nonwoven webs by electrospinning process and vapor deposition of 1H,1H,2H,2H-perfluorodecyltrichlorosilane (PFDTS) and to investigate the influence of fiber morphology and surface energy on wettability. To this end, PS webs with various fiber morphologies were electrospun under different polymer concentrations and solvent mixtures. PS substrates were treated by air plasma to attach –OH groups before the vapor deposition of PFDTS. Air plasma treatment itself increased the surface energy of PS; however, with PFDTS coating, the surface energy was decreased. The wettability was characterized by WCA and sliding angle measurement. WCAs on the electrospun webs were greater than that of flat PS film (WCA=95˚) due to the increased roughness of the web. The web with beads or grooved fibers achieved superhydrophobicity (WCA>150˚). PFDTS deposition lowered the surface energy of PS surface to about 15.8 mN/m. PS web with PFDTS deposition presented high water contact angle up to 169˚ and low sliding angle about 3˚. Also it was attempted to characterize the interfacial area between water and a solid surface on irregular fibrous webs. The fraction of solid surface area wet by the liquid (solid fraction) was observed by staining the rough electrospun web with a hydrophobic fluorescent dye, coumarin. The actual solid fraction corresponded fairly well with the theoretical solid fraction calculated by the Cassie-Baxter equation, demonstrating that the treated superhydrophobic surface follows the Cassie-Baxter wetting state.
Keywords: Electrospinning; Superhydrophobic; Polystyrene; Surface energy; Fiber morphology; Solid area fraction